Vibrational, Rotational, and Electronic Spectroscopy for Possible Interstellar Detection of AlNH2 and HAlNH - Tarek Trabelsi; Vincent J. Esposito; Joseph S. Francisco (The Astrophysical Journal, 2023)
We obtained accurate vibrational frequencies, rotational constants, and vertical transition energy for AlNH _2 (X ^1 A _1 ) and HAlNH(X ^1 A′) isomers using ab initio calculations at various levels of theory. These two isomers are potential candidates for astronomical observation. AlNH _2 and HAlNH are thermodynamically stable, with Al-NH _2 and HAl-NH bond dissociation energies predicted to be 4.39 and 3.60 eV, respectively. The two isomers are characterized by sizable dipole moments of 1.211 and 3.64 D, respectively. The anharmonic frequencies and spectroscopic constants reported for the two isomers should facilitate their experimental differentiation. In addition, we evaluated the evolution of the low-lying electronic states along the stretching coordinates, as well as the absorption cross sections. AlNH _2 absorbs strongly around 287, 249, and 200 nm, whereas the HAlNH absorption is centered around 370 and 233 nm.